Religious diversity and interreligious dialogue - Körs, Anna; Weiße, Wolfram; Willaime, Jean-Paul (Springer International Publishing, 2020)
Chapter1. Preface (Wilhelm Krull) -- Chapter2. Introduction (Anna Körs, Wolfram Weisse and Jean-Paul Willaime) -- Chapter3. The Role of Religion for Living Together in a Diverse Society (Aydan Özoguz) -- Chapter4. Toward a New Paradigm for Religion in a Pluralist Age (Peter L. Berger) -- Chapter5. Global Migration, Religious Diversity and Dialogue: Towards a Post-Westphalian Circumstance (Peter Beyer) -- Chapter6. The Established and the Newcomers. A Weberian-Bourdieusian View of Congregations in the Swiss Religious Field (Jörg Stolz and Christophe Monnot) -- Chapter7. Integration, Laïcité and Religion in France (Jean-Paul Willaime) -- Chapter8. Governance of Religious Diversity – Socio-Legal Dynamics in Europe (Matthias Koenig) -- Chapter9. Formulas of Peace? Interreligious actors and the local governance of religious diversity in Europe (Maria del Mal Griera) -- Chapter10. “Laïcité in the Make”: Negotiating Secularism and Religious Diversity in the French Local Context (Julia Martínez Ariño) -- Chapter11. Crossing the lines? Interfaith Governance as an arena of boundary work (Alexander Kenneth-Nagel) -- Chapter12. Governance of Religious Diversity in Local Context – the Case Study of Hamburg (Anna Körs) -- Chapter13. A territorial perspective on religious pluralization in Europe (Nicola Tietze) -- Chapter14. Attacks in Paris: when the France of believers rediscovers a common soul (Jonathan Richard) -- Chapter15. Narrating Stability within Interreligious Dialogue. First Results of a Qualitative Inquiry on Consequences of Plurality Experiences for Religious Identity (Gritt Klinkhammer and Anna Neumaier) -- Chapter16. Perception and Political Meaning of Religious Plurality and the Role of Media (Gert Pickel) -- Chapter17. Contribution of Religious Education to a Better Living Together in Europe (Robert Jackson) -- Chapter18. Religious Education in Contextual Perspective (Thorsten Knauth and Dörthe Vieregge) -- Chapter19. Concepts and Praxis of Inter-Religious and Socio-Religious Dialogue (Reinhold Bernhardt) -- Chapter20. Dialogue in the Public Sphere: “Not an ambulance service, but a public health programme” (Anantanand Rambachan) -- Chapter21. The Relevance of Interreligious Dialogue in the Public Sphere. Some Misgivings (Perry Schmidt-Leukel) -- Chapter22. Interreligious Dialogue in the Public Spere. An Alevi Perpective (Handan Aksünger) -- Chapter23. Interreligious Dialogue. Challenges and Prospects within a Secular State and Postsecular Society (Johannes Frühbauer) -- Chapter24. Dialogical Theology – Doing Theology Together. A Buddhist Response to the Challenge of Religious Pluralisation (Carola Roloff) -- Chapter25. Self and Other in Contemporary Buddhist Inter-Communal Relations: Engaged Buddhism, Buddhist Nationalist and Buddhist Theological Perspectives (Sallie B. King) -- Chapter26. Interreligious Encounter and Human Rights. A Jewish Vantage Point (Ephraim Meir) -- Chapter27. Dialogical Theology and Social Engagement (Paul Knitter).
Gesehen am 15.03.2024
Keywords: Aufsatzsammlung; Interreligiöser Dialog; Religiöser Pluralismus